Faces of fraud : cases and lessons from a life of fighting fraudsters - Biegelman, Martin T. (John Wiley & Sons, Inc., 2013)
BThe ultimate tool for understanding, investigating and preventing fraud/b Fraud is an evil with a life of its own that leaves a financial, repetitional, and emotional toll on its victims. While monumental scandals, such as Enron, WorldCom, and Madoff's Ponzi scheme make the front pages, fraud is a daily occurrence impacting companies and individuals alike. iFaces of Fraud/i reveals must-know characteristics of fraudsters and the skills needed to outwit them. Recognized Fraud Fighting Expert Martin Biegelman draws from his 40 years of experience fighting fraud to profile not only the key traits fraudsters share, but also the qualities fraud examiners must possess to be successful./ ulliEach chapter contains stories from actual cases that the author investigated/liliProfiles the must-know characteristics of fraudsters and the skills you'll need to outwit them/liliReveals the traits of accomplished fraud examiners/liliExplores the best practices in fraud detection, investigation and prevention to cultivate in order to maximize success/liliWritten by fraud fighting expert Martin T. Biegelman/li/ul Although fraud will never be completely eradicated, there is much that can be done to reduce the number and size of frauds that take place in any organization. Boiling down the key lessons the author has culled from his long career, iFaces of Fraud/i entertains and informs with stories from real cases the author investigated over his long career, and imparts useful tips you can start using right away in the fraud examination field.